ELABORAÇÃO DE MASSAS DE BRIGADEIRO SEM LACTOSE, PRODUZIDAS A PARTIR DE VEGETAIS - Villa , Isadora; De Carli, Eliane (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2021)
In Brazil, 70% of the population suffers, to some degree, from malabsorption or lactose intolerance, however, the market for products with a low content of this disaccharide is still not fully explored. The still reduced offer of these products, motivated the development of a new market and new processes due to the need for innovations and special characteristics for their production. With that in mind, this study aimed to elaborate and evaluate the sensory acceptability and nutritional value of lactose-free brigadeiro pasta produced from vegetables. Two formulations were made from condensed soy milk, green banana biomass and sweet potato as the main elements. The following analyzes were carried out: moisture, mineral matter, proteins and sensory analysis, according to the methodologies of Instituto Adolfo Lutz. The elaborated formulations presented good results in the sensorial evaluations, obtaining an acceptability index above 80% of the analyzed attributes. Acceptability rates were above 70% only for the odor attribute. As for the protein content, the samples showed 3.26% and 5.96% lipids. It was concluded that the development of the market for lactose-free products, with a focus on the production of brigadeiro, is possible.